English Learning Interactive Media for Early Childhood Through the Total Physical Response Method - Suryana, Dadan; Sari, Novi Engla; Winarti; Lina; Mayar, Farida; Satria, Sri (Program Studi Magister Pendidikan Anak Usia Dini, 2021)
Although there are several approaches and strategies for teaching foreign languages, the Total Physical Response (TPR) approach is the most suitable for young learners. TPR is a way of teaching language that is based on the synchronization of speech and behaviour, or in other words, teaching language through movement. This study aims to develop English learning media for children through the Total Physical Response (TPR) method. This study uses a Research and Development (R & D) approach. The development model used is the ADDIE development model (analysis, design, development, implementation, and evaluation). Data collection techniques in this study were based on the results of expert validation tests, media practicality tests, and media effectiveness tests on children aged 5-6 years in Kindergarten. The results showed that the validity test of developing interactive media for children's English learning through the TPR method by media expert was declared valid with the result of 93%. The validity test on the material aspect shows the result is 98%. In the language aspect, the language expert gave the results of the feasibility of the language used in the media with a value of 96%. Likewise, with the practicality test, the results showed that the media had an average value of practicality with a percentage of 94%. The most important result in media development is determined by the results of the effectiveness test, and this media gets an average percentage score of 77.8% on the media tested on children. Therefore, interactive media for children's English learning through the Total Physical Response method deserves to be used as interactive and quality learning media that is practical and effective for early childhood. Intervention in introducing how to develop interactive media for learning English to teachers can be carried out in further research. Keywords: Early Childhood, English Learning Media, Total Physical Response (TPR) method References: Amri, S. (2013). Pengembangan & Model Pembelajaran Dalam Kurikulum. Prestasi Pustakarya. Andi. (2013). Kupas Tuntas Adobe Flash CS6. Gramedia. Ariani, N. & H. (2010). Pembelajaran Multimedia di Sekolah Pedoman Pembelajaran Inspiratif, Konstruktif, dan Prospektif. Prestasi Pustakarya. Arsyad, A. (2011). Media Pembelajaran. Raja Grafindo Persada. Asher, J. J. (1969). The Total Physical Response Approach to Second Language Learning. The Modern Language Journal, 53(1), 3. https://doi.org/10.2307/322091 Astutik, Y., & Aulina Choirun, N. (2017). Total Physical Response (Tpr) Pada Pengajaran Bahasa Inggris Siswa Taman Kanak-Kanak. Jurnal Pendidikan Bahasa Dan Sastra, 17(2), 196–2017. Chaer, A. (2009). Psikolinguistik Kajian Teoretik. Rineka Cipta. Cheng, G. (2009). Using Game Making Pedagogy to Facilitate Student Learning of Interactive Multimedia. Australasian Journal Educational Technology, Vol. 25 (2, 204–220. Danim. (2008). Media Komunikasi Pendidikan. Bumi Aksara. Dardjowidjojo, S. (2010). Psikolinguistik: Pengantar Pemahaman Manusia Edisi Kedua. Yayasan Obor Indonesia Unika Atma Jaya. Darmawan, D. (2012). Inovasi Pendidikan. Remaja Rosdakarya. Daryanto. (2011). Media Pembelajaran. PT. Sarana Tutorial Nurani Sejahtera. Depdiknas. (2009). Peraturan Menteri Pendidikan Nasional Republik Indonesia Nomor 58 Tahun 2009 tentang Standar Pendidikan Anak Usia dini. Er, S. (2013). Using Total Physical Response Method in Early Childhood Foreign Language Teaching Environments. Procedia - Social and Behavioral Sciences, 93, 1766–1768. https://doi.org/10.1016/j.sbspro.2013.10.113 Fauzi, C., & Basikin. (2020). The Impact of the Whole Language Approach Towards Children Early Reading and Writing in English. JPUD - Jurnal Pendidikan Usia Dini, 14(1), 87–101. https://doi.org/10.21009/jpud.141.07 Hanafiah, Nanang & Cucu, S. (2010). Konsep Strategi Pembelajaran. Refika Aditama. Jackman Hilda, L. (2010). Childhood Education Curriculum: A Child’s Connection to The world. Nelson Education Ltd. Jared, K., & Grace, O. (2009). Technology Interaction Profeesional Development Model for Practicing Teachers. Journal Technology and Early Childhood Education, 37, 209–218. Komalasari, K. (2010). Pembelajaran Kontekstual: Konsep dan Aplikasi. Refika Aditama. Larsen-Freeman, D., & Anderson, M. (2011). Techniques and principles in language teaching (3rd ed). Oxford University Press. Lase, F. (2017). Hakikat Pendidikan Berdasarkan Kebutuhan Usia. . . Jurnal PPKn & Hukum, 12(1). Mayesky. (2012). Creative Activities for Young Children. Nelson Education. Mohamad Syarif Sumantri. (2015). Strategi Pembelajaran: Teori dan Praktik di Tingkat Pendidikan Dasar. PT Raja Grafindo Persada. Ghani, N. H. H. M. G. (2014). The Effectiveness of Total Physical Response (TPR ) Approach in Helping Slow Young Learners With Low. International Journal of Research in Social Sciences, 4(6). Mulia Dewi. (2016). Thesis the Role of Play in Teaching English as A Foreign Language in Early Childhood Settings in Indonesia. Australia: Deakin University. Munir. (2009). Multimedia Konsep dan Aplikasi dalam Pendidikan. Alfabeta. Munir. (2012). Multimedia Konsep dan Aplikasi dalam Pendidikan. Alfabeta. Nuraeni, C. (2019). Using Total Physical Response (TPR) Method on Young Learners English Language Teaching. Metathesis: Journal of English Language, Literature, and Teaching, 3(1), 26. https://doi.org/10.31002/metathesis.v3i1.1223 Paturan Menteri Pendidikan Repuberlik Indonesia Nomor 137. (2014). Tentang Standar PAUD. Peraturan Menteri Pendidikan dan Kebudayaan RI No. 146 Tahun 2014 Tentang Implementasi Kurikulum 2013 PAUD. (2014). Pinter, A. (2006). Teaching young language learners. Oxford University Press. Pranowo, G. (2011). Kreasi Animasi Interaktif dengan Action Script 3.0 pada Flash CS6. Graha Ilmu. Priscilla, C. (2009). Supporting Children Learning English as Second Language in the Early Years (Birth to Six Years). Australia: Victorian Curriculum and Assessment Authority. Purwanti, R. (2020). Pembelajaran Bahasa Inggris Untuk Anak Usia Dini Melalui Metode Gerak dan Lagu. Potensia, Jurnal Ilmiah, 5(2), 91–105. Putro, W. E. (2013). Teknik Penyusunan Instrumen Penelitian. Pustaka Pelajar. Rahmat, A. (2010). Implementasi Kurikulum Bahasa Asing di Taman-Kanak (TK) DKI Jakarta. Jurnal Kajian Linguistik Dan Sastra, 22(77–10), 1. Richards, J. C., & Rodgers, T. S. (2001). Approaches and methods in language teaching. Cambridge University Press. Riduwan. (2012). Skala Pengukuran Variabel-Variabel Penelitian. Alfabeta. Sanjaya, W. (2009). Strategi Pembelajaran. Kencana. Santrock, Jhon. W. (2011). - Span Development: Perkembangan Masa Hidup. Erlangga. Sari, N. E., & Suryana, D. (2019). Thematic Pop-Up Book as a Learning Media for Early Childhood Language Development. JPUD - Jurnal Pendidikan Usia Dini, 13(1), 43–57. https://doi.org/10.21009/10.21009/jpud.131.04 Savic, V. (2014). Total Physical Response Activities in Teaching English to Young Learners. Journal of Physical Culture and Modern Society, 17, 447–454. Setiawan Deni dkk. (2017). Pengaruh Media Pembelajaran Dan Motivasi Belajar Terhadap Hasil Belajar Desain Sistem Instruksional Pendekatan Tpack. Jurnal Teknologi Dan Informasi Dalam Pendidikan, Vol 4 No 2, 141–146. Stakanova E., & Tolstikhina, E. (2014). Different Approaches to Teaching English As A Foreign Language to Young Learner. . . Journal of Procedia Social and Behaviour Science, Vol. 146, 456–460. Suryana, D. (2016). Stimulasi dan Aspek Perkembangan Anak. Kencana. Suyadi. (2013). Konsep Dasar PAUD. Rosdakarya. Suyanto. (2008). Evolutionary Computation. Informatika. Tarigan, H. G. (2009). Pengajaran kedwibahasaan. Angkasa. Wijayatiningsih, & Mulyadi. (2014). Pemanfaatan model total physical response dan repetition untuk pengembangan pembelajaran bahasa Inggris anak usia dini / TK. Jurnal Penelitian Pendidikan, 31(1), 63–66. Wiyani, N. A. (2014). Perkembangan Anak Usia Dini: Panduan Orang Tua dan Pendidik PAUD Dalam Memahami serta mendidik Anak Usia Dini. Gava Media.